Performance Analysis of Millennial Generation Civil Apparatus in The National Unity and Regional Political Agency of Central Sulawesi Province - Putri Syifarani, Athiyah; Irfan Mufti, Moh.; Chaeriah Ahsan, Sitti; Nuraisyah, Nuraisyah; Haryono, Dandan (International Journal of Social Science, Education, Communication and Economics, 2024)
Performance can be explained as the level of evaluation or achievement of individual work results in the context of the work relationship between the individual and the organization. The millennial generation as a group was born between 1982 and 2000. They are a generation that grew up with technology and tend to prioritize balance between work and personal life. The organizational performance of the National Unity and Political Agency of Central Sulawesi Province in 2020 to 2022 received a weight below that determined by the Regional Inspectorate of Central Sulawesi Province with a value in 2020 of 9.25%, in 2021 of 9.25% and in 2022 of 22. 5%. The aim of this research is to determine the performance of the Millennial Generation ASN in the National Unity and Political Agency of Central Sulawesi Province. The research method used is a descriptive qualitative method, by emphasizing performance indicators according to Robbins, namely, Work Quality, Quantity, Timeliness, Effectiveness, Independence, and Commitment. The data used are primary and secondary data through interviews, observation, and documentation studies. The data analysis techniques that researchers carry out are data condensation, data presentation and describing and drawing conclusions. The results of the research show that the performance of the Millennial Generation ASN in the National Unity and Political Agency of Central Sulawesi Province based on the indicator assessment from Robbins can be said to be good with the target being implemented optimally. However, what makes organizational performance low is because there are several obstacles, one of which is that the number of ASNs is not commensurate with the organization's workload.